2004
DOI: 10.1093/bioinformatics/bth378
|View full text |Cite
|
Sign up to set email alerts
|

BioNetGen: software for rule-based modeling of signal transduction based on the interactions of molecular domains

Abstract: BioNetGen allows a user to create a computational model that characterizes the dynamics of a signal transduction system, and that accounts comprehensively and precisely for specified enzymatic activities, potential post-translational modifications and interactions of the domains of signaling molecules. The output defines and parameterizes the network of molecular species that can arise during signaling and provides functions that relate model variables to experimental readouts of interest. Models that can be g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
386
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 386 publications
(392 citation statements)
references
References 11 publications
0
386
0
Order By: Relevance
“…YPM also contains a synonymous embedded model of the pheromone system encoded in the BioNetGen language (27). We manually simplified the full pheromone response system model encoded in the YPM to eliminate molecules and reaction rules that were not directly involved in the MAPK cascade (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…YPM also contains a synonymous embedded model of the pheromone system encoded in the BioNetGen language (27). We manually simplified the full pheromone response system model encoded in the YPM to eliminate molecules and reaction rules that were not directly involved in the MAPK cascade (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Inclusion of Ste5 dimerization would have increased the number of species in the model from 236 to over 20,000, dramatically slowing down simulation and hindering parameter estimation. We wrote MATLAB scripts that used a genetic algorithm (Genetic Algorithm and Direct Search Toolbox, v2.1, R2007a; MathWorks) to perform parameter optimization and execute BioNetGen (version 2.0.46) (27) simulations of the models (SI Materials and Methods). We varied abundances over the wide range of 10-10 6 molecules to explore the full potential of the pathway architecture rather than limiting ourselves to abundances that could easily be achieved experimentally.…”
Section: Measurement Of Fluorescent Protein Fusions and Reporter Genementioning
confidence: 99%
“…We also encoded the model in the BioNetGen™ language (Faeder et al, 2005a;Blinov et al, 2006), which enables automatic building (and solution) of ODEs based on specified reaction rules that serve as generators of chemical reactions. This formal model specification can be used for future work as the BioNetGen™ software allows for simulations of systems of thousands of reactions (Blinov et al, 2004;Faeder et al, 2005b). We found that the stochastic simulations performed using BioNetGen™ are more than 10 times faster than in MATLAB.…”
Section: Numerical Implementation and Simulation Protocolsmentioning
confidence: 99%
“…The "don't care, don't write" approach adopted in the Kappa-calculus, as well as in other rule-based languages like BioNetGen [4], opened the way for introducing compositional modeling in rule-based process calculi, and provides very compact and readable descriptions of biochemical systems in the presence of sophisticated molecule bindings. While compositional modeling represents in general a desirable advantage in the hands of the modeler, it becomes a limit when important properties of the system cannot be described in a compositional calculus because of their intrinsic non-compositionality.…”
Section: Resultsmentioning
confidence: 99%